2020
DOI: 10.3389/fneur.2020.00748
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable Outcomes Related to Endovascular Treatment of Giant Vertebrobasilar Aneurysms

Abstract: Background: Giant vertebrobasilar aneurysms (GVBAs) have an unfavorable natural history if left untreated and often pose a sizeable challenge to endovascular treatment. The aim of this study was to analyze the angiographic and clinical outcomes of GVBAs treated by various endovascular procedures. Methods: Between January 2010 and September 2018, 27 patients with 27 GVBAs treated endovascularly were enrolled in this consecutive study. The clinical and angiographic features, treatment modalities, and outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
(32 reference statements)
2
10
0
Order By: Relevance
“…The concomitant coiling was needed to facilitate the aneurysmal occlusion and prevent the rupture of aneurysms. For large or giant vertebrobasilar aneurysms treated with stent-assisted coiling, Li et al [ 24 ] reported a recurrence rate of 33.3%, while Mu and colleagues [ 25 ] reported a recanalization rate of 66.6%, with a complication rate of 36.4%. In our study, the complete occlusion rate was 54.2% during the follow-up after stent-assisted coiling, and the SAE rate was 15.4%, including mortality of 3.9%.…”
Section: Discussionmentioning
confidence: 99%
“…The concomitant coiling was needed to facilitate the aneurysmal occlusion and prevent the rupture of aneurysms. For large or giant vertebrobasilar aneurysms treated with stent-assisted coiling, Li et al [ 24 ] reported a recurrence rate of 33.3%, while Mu and colleagues [ 25 ] reported a recanalization rate of 66.6%, with a complication rate of 36.4%. In our study, the complete occlusion rate was 54.2% during the follow-up after stent-assisted coiling, and the SAE rate was 15.4%, including mortality of 3.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-aneurysmal thrombus resolution and coil migration into the thrombus mass may attribute to the aneurysm residual or the aneurysm recurrence (18). Previous studies have reported that the endovascular treatment of large or giant vertebrobasilar aneurysms was related to relatively unfavorable angiography outcomes, with higher recurrence and retreatment rates as compared to aneurysms located in anterior circulations (18,25,26). Our results were similar to those of Liang et al (17), who reported a complete occlusion rate of 74.1% at the median follow-up duration of 6.8 months, in the cohort of 103 large or giant posterior circulation aneurysms treated with endovascular management.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the limited surgical accessibility and relatively high mortality of open surgical procedures, endovascular reconstructive therapies, including SAC and FD, have been increasingly used. FD has been attempted to apply in the treatment of intradural large VBA aneurysms, but the results regarding the safety and efficacy remain controversial, as compared to SAC ( 7 , 16 , 17 ). We aimed to compare the treatment outcomes of FD and SAC for the treatment of intradural large VBA aneurysms.…”
Section: Discussionmentioning
confidence: 99%